The CLEAR X‐ray emission spectrometer available at the CLAESS beamline of ALBA synchrotron. (24th November 2022) - Simonelli, L.; Marini, C.; Ribo, L.; Homs, R.; Avila, J.; Heinis, D.; Preda, I.; Klementiev, K.
Abstract : The CLEAR emission spectrometer, a valid option with respect to other existing ones, is described. Abstract : The CLEAR X‐ray emission spectrometer installed at the CLAESS beamline of the ALBA synchrotron is described. It is an energy‐dispersive spectrometer based on Rowland circle geometry with 1 m‐diameter circle. The energy dispersion is achieved by the combination of a diced analyzer crystal and a unidimensional detector. A single unconventional dynamically bent analyzer crystal (Si 111) permits a wide energy range to be covered, just by exploiting its different reflections (333, 444, 555, 777, 888): 6–22 keV, with a spectrometer efficiency that decreases above 11 keV because of the Si detector thickness (Mythen, 350 µm), while the relative scattering intensities for the Si 333, 444, 555, 777 and 888 reflections correspond to 36, 40, 21, 13 and 15, respectively. The provided energy resolution is typically below 1–2 eV and depends on the beam size, working Bragg angle and reflection exploited. In most cases the energy dispersion ranges from 10 to 20 eV and can be enlarged by working in the out‐of‐Rowland geometry up to 40 eV. The spectrometer works in full backscattering geometry with the beam passing through the two halves of the analyzer. The vacuum beam path and the particular geometry allow a typical average noise of only 0.5 counts per second per pixel. The spectrometer is mainly used for measuring emission lines and high‐resolution absorption spectra, with a typical scanning time for highly concentrated systems of around half an hour, including several repeats. The intrinsic energy dispersion allows systematic collection of resonant X‐ray emission maps by measuring high‐resolution absorption spectra. Moreover, it allows spectra to be measured on a single‐shot basis. Resonant inelastic X‐ray scattering experiments to probe electronic excitations are feasible, although the spectrometer is not optimized for this purpose due to the limited energy resolution and scattering geometry provided. In that case, to minimize the quasi‐elastic line, the spectrometer is able to rotate along the beam path. Advantages and disadvantages with respect to other existing spectrometers are highlighted.